The integration of multiple intelligences theory and TAI cooperative learning for teaching Calculus for Engineering 1 for bachelor’s degree students - Chanokgan Sahatsathatsana; Sattra Sahatsathatsana; Wirawan Heman (Journal of Green Learning, 2021)
The purposes of this study were (1) to compare the pre and post-tests scores of learning through the developed lesson plans based on the theory of multiple intelligences and TAI cooperative learning, and (2) to evaluate the students’ satisfaction on learning through the developed lesson plans based on the theory of multiple intelligences and TAI cooperative learning. The subjects were 41 students of the Faculty of Engineering and Industrial Technology who enrolled in the Calculus for Engineering 1 subject in the first semester of the 2019 academic year received from cluster random sampling. The research instruments were lesson plans, learning achievement test, and a questionnaire on students’ satisfaction. The results revealed that : the mean score of the post-test on the topic of differentiation of algebraic functions was significantly higher than mean score of the pre-test at the level of .05. The mean score of the students’ satisfaction on learning through the developed lesson plans was at the highest level.